Hepatitis C virus lacking the hypervariable region 1 of the second envelope protein is infectious and causes acute resolving or persistent infection in chimpanzees - Forns, Xavier (The National Academy of Sciences, 2000)
Persistent infection with hepatitis C virus (HCV) is among the leading causes of chronic liver disease. Previous studies suggested that genetic variation in hypervariable region 1 (HVR1) of the second envelope protein, possibly in response to host immune pressure, influences the outcome of HCV infection. In the present study, a chimpanzee transfected intrahepatically with RNA transcripts of an infectious HCV clone (pCV-H77C) from which HVR1 was deleted became infected; the ΔHVR1 virus was subsequently transmitted to a second chimpanzee. Infection with ΔHVR1 virus resulted in persistent infection in the former chimpanzee and in acute resolving infection in the latter chimpanzee. Both chimpanzees developed hepatitis. The ΔHVR1 virus initially replicated to low titers, but virus titer increased significantly after mutations appeared in the viral genome. Thus, wild-type HCV without HVR1 was apparently attenuated, suggesting a functional role of HVR1. However, our data indicate that HVR1 is not essential for the viability of HCV, the resolution of infection, or the progression to chronicity.